Dispositional optimism, optimism priming, and prevention of ego depletion. (31st July 2014) - In Den Bosch‐Meevissen, Yvo M. C.; Peters, Madelon L.; Alberts, Hugo J. E. M.
Abstract Exerting self‐control leads to a diminished capacity to carry out successive acts of self‐control, a process termed ego depletion. The present study investigated whether dispositional optimism, priming of an optimistic orientation, or their interaction can counteract the ego depletion effect. A total of 160 participants performed a self‐control‐demanding weight‐lifting task on two occasions. Half of the participants were depleted between the two weight‐lifting tasks. Because depletion of self‐regulatory resources can undermine optimism half of the participants in the depletion, and no‐depletion condition were primed for an optimistic orientation before performing the second self‐control task. Results demonstrated an interaction between dispositional optimism and optimism priming. Only in participants high in dispositional optimism did the optimism prime lead to undiminished persistence on the weight‐lifting task. These results demonstrate that dispositional optimism may lead to improved goal persistence in the face of adversity only under conditions in which optimistic schemas are activated. Copyright © 2014 John Wiley & Sons, Ltd.